BUDAYA DEMOKRASI PADA OSIS - Budi Cahyono; Raden Gunawan Sudarmanto; Risma Margaretha Sinaga (Faculty of Teacher Training and Education, University of Lampung, 2014)
This research aims to assess the cultural democracy in the intra-school student organization and the school's role in the development of a democratic culture. The method used in this research is a qualitative, by using case study approach. The results of this research is the development of a democratic culture in the intra-school student organization run well by implementing of culture or democratic values of tolerance on intra-school student organization namely, freedom of speech, open, communication, respect each other and togetherness. Development of democratic culture in the council supported the existence of mutual respect differences, teachers who teach tolerance, confident attitude in the opinion of students, discipline, loyalty to the organization, mutual trust and realize common interests. Constraints in the development of a democratic culture is not confident in expressing an opinion on students, authoritarian and arrogant attitude of the school, the attitude is not willing to accept other people's opinions and attitudes of feeling amazing compared to their friends.Penelitian ini bertujuan untuk mengkaji budaya demokrasi yang terdapat pada organisasi siswa intra sekolah dan peran sekolah dalam pengembangan budaya demokrasi. Metode yang digunakan pada penelitian ini adalah kualitatif dengan pendekatan studi kasus. Hasil penelitian ini menyatakan bahwa pengembangan budaya demokrasi berjalan baik dengan dilaksanakannya kultur atau nilai-nilai demokrasi pada OSIS yaitu toleransi, kebebasan berpendapat, keterbukaan, komunikasi, saling menghargai dan kebersamaan. Pengembangan budaya demokrasi pada OSIS didukung adanya sikap saling menghargai perbedaan, guru yang mengajarkan sikap toleransi, sikap percaya diri siswa dalam berpendapat, disiplin, loyalitas pada organisasi, saling percaya dan menyadari kepentingan bersama. Hambatan dalam pengembangan budaya demokrasi adalah tidak percaya diri dalam menyampaikan pendapat pada diri siswa, sikap otoriter dan arogan dari pihak sekolah, sikap tidak mau menerima pendapat orang lain serta sikap merasa luar biasa dibanding teman-temannya.Kata kunci: budaya, demokrasi, organisasi siswa intra sekolah